2007
DOI: 10.1002/elan.200603819
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Catalytic Processes with Hydrogen Peroxide Showing Oxidative and Reductive Properties (Acting as Oxidant or Reductant)

Abstract: It has been found that hydrogen peroxide can act as an oxidant and as a reductant of transition metal complexes in acetonitrile. Therefore, the examples of catalytic currents of oxidants and reductants has been described. In the case of Co(acac) 3 both the types of catalytic currents are present in a single cyclic-voltammetric scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Electrochemically and chemically reversible redox processes are theoretically characterized by a peak separation of DE p = 0.059 V and peak current ratio of one, respectively [31][32][33]. The assignment of the redox couples as well as the redox values are in good agreement with previously published results; see Table 2 for a summary [4,[9][10][11][12]14]. We also observe that the redox potentials vs ferrocene as reference system, vary with the nature of the solvent; see Table 2 and Table S1 to compare data of Mn(CH 3 COCHCOCH 3 ) 3 , complex (2), in both CH 3 CN and DCM as solvent.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Electrochemically and chemically reversible redox processes are theoretically characterized by a peak separation of DE p = 0.059 V and peak current ratio of one, respectively [31][32][33]. The assignment of the redox couples as well as the redox values are in good agreement with previously published results; see Table 2 for a summary [4,[9][10][11][12]14]. We also observe that the redox potentials vs ferrocene as reference system, vary with the nature of the solvent; see Table 2 and Table S1 to compare data of Mn(CH 3 COCHCOCH 3 ) 3 , complex (2), in both CH 3 CN and DCM as solvent.…”
Section: Resultssupporting
confidence: 59%
“…Considering different Mn(b-diketonato) 3 complexes, it seems as if, with only one exception [8], Mn(CH 3 COCHCOCH 3 ) 3 (2), is the only Mn(b-diketonato) 3 complex that has previously been studied by electrochemistry [4,[9][10][11][12][13][14]. In this study we therefore present an electrochemical study of a series of four new and five known Mn(b-diketonato) 3 complexes, with b-diketonato = dpm (1), acac (2), ba (3) (new), dbm (4), tfaa (5) (new), tfth (6) (new), tffu (7), tfba (8) (new) and hfaa (9), see Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…The process of electroreduction of hydrogen peroxide at the surface of Cu-CPE is similar to that of the bromate and the nitrite. The following catalytic scheme showed that the copper-complex catalyzed hydrogen peroxide reduction [51].…”
Section: Electrocatalytic Effect On Reduction Of Hydrogen Peroxidementioning
confidence: 99%
“…The at band, E  , values were estimated by extending the linear t line from 1/C 2 versus E plot. The E  of ZnS, SnIn 4 S 8 and ZnS/SnIn 4 S 8 NPs were determined to be À0.77, À1.33 and À1.21 V vs. SCE respectively which are corresponding to À0.53, À1.10 and À0.97 V vs. NHE respectively as E (NHE) ¼ E (SCE) + 0.242 V. 29 The potential for ntype semiconductors is substantially higher by 0.1-0.3 eV, depending on the effective electron mass and carrier concentration than the at band potential. 30 The difference in potentials between conduction and at bands has been set at 0.2 eV in this experiment.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%